Distinct effects of RGD-glycoproteins on integrin-mediated adhesion and osteogenic differentiation of human mesenchymal stem cells - Baha-Schwab, Elisabeth H.; Halbig, Maria; Glenske, Kristina; Wagner, Alena-Svenja; Wenisch, Sabine; Cavalcanti-Adam, Elisabetta A. (International journal of medical sciences, 2013)
The detailed interactions of mesenchymal stem cells (MSCs) with their extracellular matrix (ECM) and the resulting effects on MSC differentiation are still largely unknown. Integrins are the main mediators of cell-ECM interaction. In this study, we investigated the adhesion of human MSCs to fibronectin, vitronectin and osteopontin, three ECM glycoproteins which contain an integrin-binding sequence, the RGD motif. We then assayed MSCs for their osteogenic commitment in the presence of the different ECM proteins. As early as 2 hours after seeding, human MSCs displayed increased adhesion when plated on fibronectin, whereas no significant difference was observed when adhering either to vitronectin or osteopontin. Over a 10-day observation period, cell proliferation was increased when cells were cultured on fibronectin and osteopontin, albeit after 5 days in culture. The adhesive role of fibronectin was further confirmed by measurements of cell area, which was significantly increased on this type of substrate. However, integrin-mediated clusters, namely focal adhesions, were larger and more mature in MSCs adhering to vitronectin and osteopontin. Adhesion to fibronectin induced elevated expression of α5-integrin, which was further upregulated under osteogenic conditions also for vitronectin and osteopontin. In contrast, during osteogenic differentiation the expression level of β3-integrin was decreased in MSCs adhering to the different ECM proteins. When MSCs were cultured under osteogenic conditions, their commitment to the osteoblast lineage and their ability to form a mineralized matrix in vitro was increased in presence of fibronectin and osteopontin. Taken together these results indicate a distinct role of ECM proteins in regulating cell adhesion, lineage commitment and phenotype of MSCs, which is due to the modulation of the expression of specific integrin subunits during growth or osteogenic differentiation.
Gesehen am 02.08.2021